#TITLE_ALTERNATIVE# - KAMAL (NIM 13204246), MUSTAPA
Production cost calculation can be done in several ways, such as using probabilistic method. Calculation using probabilistic methode differ from deterministic methode which is all of generation unit need to be operated in probabilistic methode due to random forced outage generation unit. The calculation is started by determining load level. Probability load level calculate from their duration in system. Cumulatif distribution function can be calculate from Probability load level. Probability production cost calculation uses unserve load method. This method is done by using convolution between Cumulatif distribution function and availability factor of each generation unit according to economic dispatch. This convolution produce new unserved load which have smaller value. Generated energy of each generation unit is difference before and after generation unit operated. Total generation cost is addition variable and fixed cost.